SISTEM PENDUKUNG KEPUTUSAN DENGAN MENGGUNAKAN METODE ELECTRE DALAM MENENTUKAN PENERIMA PROGRAM INDONESIA PINTAR (PIP) MELALUI KARTU INDONESIA PINTAR (KIP) (STUDI KASUS: SD SWASTA AL â WASHLIYAH MOHO KABUPATEN SIMALUNGUN) - Ningsih, Sri Rahayu; Damanik, Irfan Sudahri; Gunawan, Indra; Saputra, Widodo (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2017)
The Smart Indonesia Program (SIP) is a government-funded education assistance program for all school-aged children (6-21 years old) or from poor and vulnerable families (eg from families / household holders of prosperous family cards / PFC) or children who fulfill Predefined criteria. Smart Indonesia Program through Smart Card Indonesia (SCI) is part of the improvement of the Poor Student Support Program (PSSP) since late 2014. The author takes a case study on SD SWASTA ALWASHLIYAH Moho. SD SWASTA ALWASHLIYAH Moho is one of the primary schools in Simalungun regency that get SIP programs for students who are less able and have difficult economic constraints. This research is based on the problem of giving Smart Indonesia Card where the process of handling aid sometimes does not match the target or target. Invalid data causes errors in SIC divisions that should be given to eligible recipients. To overcome these problems required Decision Support System (DSS) is expected to solve problems in the provision of KIP with Electre method. The Electre method is a multicriteria decision-making method based on each appropriate criterion. The criteria used are: Parent Job, Elderly Income, The Number of Dependents, Number of Dependents Still Schooled, Raport Value, KKS Holders, Child Status, Residence, Type of Home. DSS SIP is only a recommendation decision to the school, for the next process handed back to the school.